Peran Kantor Pelayanan Kekayaan Negara dan Lelang (KPKNL) Dalam Menjamin Keadilan dan Kepastian Hukum Lelang Negara - Angreinni Angreinni; Zaenal Arifin; Albertus Heru Nuswanto; Muhammad Iftar Aryaputra; Putri Haliza Yuniar (JURNAL USM LAW REVIEW, 2025)
This study aims to analyze the role of the State Assets and Auction Service Office (KPKNL) in ensuring fair auction implementation from regulatory, procedural, and stakeholder-protection perspectives. The research is motivated by the persistence of auction disputes, participant dissatisfaction, and negative perceptions regarding transparency and accountability in state auction practices. Previous studies have primarily examined auction procedures, transparency, or protection of specific parties in isolation, and therefore have not provided a comprehensive analysis of KPKNL as an institutional actor that integrates legal certainty, legal protection, and substantive fairness throughout the auction process. This research employs a normative juridical method using statutory, conceptual, and case approaches, supported by analysis of primary and secondary legal materials as well as secondary empirical data on auction practices. The findings indicate that KPKNL plays a strategic role as a technical regulator, process facilitator, and guarantor of compliance with transparency, accountability, and legal protection principles for all stakeholders. However, the effectiveness of these functions remains limited by challenges in public outreach, information technology utilization, and complaint-handling mechanisms. Academically, this study contributes to a more integrated understanding of KPKNL’s institutional function in ensuring auction fairness. Practically, it highlights the need to strengthen institutional capacity, enhance auction digitalization, and refine regulatory frameworks to improve governance quality and public trust in state auction systems. Penelitian ini bertujuan menganalisis peran Kantor Pelayanan Kekayaan Negara dan Lelang (KPKNL) dalam menjamin pelaksanaan lelang yang berkeadilan dari aspek regulasi, prosedur, dan perlindungan para pihak. Penelitian ini dilatarbelakangi oleh masih ditemukannya sengketa lelang, ketidakpuasan peserta, serta persepsi negatif terhadap transparansi dan akuntabilitas pelaksanaan lelang negara. Kajian terdahulu umumnya menelaah prosedur lelang, transparansi, atau perlindungan pihak tertentu secara parsial, sehingga belum memberikan analisis komprehensif mengenai peran KPKNL sebagai institusi yang mengintegrasikan kepastian hukum, perlindungan hukum, dan keadilan substantif dalam keseluruhan tahapan lelang. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan, konseptual, dan kasus, yang didukung oleh analisis bahan hukum primer, sekunder, serta data empiris sekunder mengenai praktik pelaksanaan lelang. Hasil penelitian menunjukkan bahwa KPKNL memiliki peran strategis sebagai regulator teknis, fasilitator proses, dan penjamin kepatuhan terhadap prinsip transparansi, akuntabilitas, serta perlindungan hukum bagi para pihak. Namun demikian, pelaksanaan fungsi tersebut belum optimal karena masih terdapat kendala pada aspek sosialisasi, pemanfaatan teknologi informasi, dan mekanisme pengaduan. Secara akademik, penelitian ini memperkuat pemahaman mengenai fungsi kelembagaan KPKNL dalam kerangka keadilan lelang yang terintegrasi. Secara praktis, penelitian ini menegaskan perlunya penguatan kapasitas kelembagaan, digitalisasi lelang, dan penyempurnaan regulasi guna meningkatkan kualitas tata kelola dan kepercayaan publik terhadap lelang negara.
Keywords: Keadilan Lelang; KPKNL; Perlindungan Hukum; Tata Kelola Lelang; Transparansi